Ascites resulting from a ruptured perinephric pseudocyst associated with a renal cyst in a dog. Issue 1 (10th January 2014) - Orioles, M.; Di Bella, A.; Merlo, M.; Ter Haar, G.
Abstract : A three‐year‐old female spayed labrador retriever was presented with progressive abdominal enlargement due to ascites. Clinical examination, clinical pathology, diagnostic imaging and explorative laparotomy findings were suggestive of the contemporary presence of a ruptured perinephric pseudocyst, and an intraparenchymal renal cyst in the right kidney. The dog recovered well after exploratory celiotomy with complete resection of the pseudocyst and nephrectomy, and clinical signs resolved completely. Histopathology revealed the concomitant presence of a renal cyst, lined by epithelium of tubular origin, with a pseudocystic structure adjacent to the kidney. A congenital origin of these lesions was suggested. To the authors' knowledge, this is the first report describing ascites as the clinical presentation of a ruptured perinephric pseudocyst in a dog. Although rare, it should be considered as a differential diagnosis in dogs presenting with ascites.